Integrated Characterization of lncRNA-Immune Interactions in Prostate Cancer - Hu, Wei; Wang, Yanru; Fang, Zhixiao; He, Wei; Li, Shengli (Frontiers in Cell and Developmental Biology, 2021)
Prostate cancer is among the top mortality factors in male around the world. Long non-coding RNAs (lncRNAs) have been shown to play crucial roles in tumor biology and immunology. However, lncRNA-immune interactions have not yet examined in prostate cancer. Here, we performed integrated analysis to characterize lncRNA-immune interactions in prostate cancer through multidimensional aspects, including immune-related hallmarks, tumor immunogenomic signatures, immune-related biological processes, immune cells, and immune checkpoints. We dissected the dysregulation of lncRNAs and their clinical relevance in prostate cancer, such as RP11-627G23.1 and RP11-465N4.5. Immune-related hallmarks took up the major parts among top significant lncRNA-hallmark interactions. Our analysis revealed that TGF-β signaling pathway was the most frequent to associate with lncRNAs, which is a signature of immune response in cancer. In addition, immune response and its regulation were the most closely connected immunological processes with lncRNA, implying the regulatory roles of lncRNAs on immune response in prostate cancer. We found that memory resting CD4+ T cells were the most lncRNA-correlated immune cell. LINC00861 was found to be potentially intervening targets of immunotherapy for prostate cancer patients, which was significantly associated with PD-1 and CTLA4. Collectively, we offered a handy resource to investigate regulatory roles of lncRNAs on tumor immunology and the development of clinical utility of lncRNAs in prostate cancer.